Imaging and EISCAT radar measurements of an auroral prebreakup event - Safargaleev, V.; Turunen, T.; Lyatsky, W.; Manninen, J.; Kozlovsky, A. (Annales Geophysicae, 1996)
The results of coordinated EISCAT and TV-camera observations of a prebreakup event on 15 November 1993 have been considered. The variations of the luminosity of two parallel auroral arcs, plasma depletion on the poleward edge of one of these arcs as well as electron and ion temperatures in front of a westward travelling surge were studied. It was found that a short-lived brightening of a weak zenith arc before an auroral breakup was accompanied by fading of an equatorial arc and, vice versa. A plasma depletion in the E region was detected by the EISCAT radar on the poleward edge of the zenith arc just before the auroral breakup. The plasma depletion was associated with an enhancement of ion (at the altitudes of 150–200 km) and electron (in E region) temperatures. During its occurrence, the electric field in the E-region was extremely large (~150 mV/m). A significant increase in ion temperature was also observed 1 min before the arrival of a westward travelling surge (WTS) at the radar zenith. This was interpreted as the existence of an extended area of enhanced electric field ahead of the WTS.